Effects of mixtures of anticancer drugs in the benthic polychaete Nereis diversicolor - da Fonseca, Tainá Garcia [UNESP]; Abessa, Denis M.S. [UNESP]; Bebianno, Maria João (Elsevier, 2019)
The increasing consumption of anticancer drugs through single and/or combinatory chemotherapy worldwide raised concern regarding their toxicity burden in coastal zones. The toxicity of a mixture of three compounds involving the drugs cisplatin (CisPt), cyclophosphamide (CP) and tamoxifen (TAM) was determined on the marine polychaete Nereis diversicolor exposed to an increasing range of their concentrations, respectively: Mix A: 0.1 + 10 + 0.1 ng L−1; Mix B: 10 + 100 + 10 ng L−1; Mix C: 100 + 500 + 25 ng L−1; Mix D: 100 + 1000 + 100 ng L−1. Different endpoints were assessed, including disturbance in the burrowing behaviour, neurotoxicity (acetylcholinesterase – AChE activity), antioxidant enzymes (superoxide dismutase – SOD; catalase – CAT; selenium-dependent glutathione peroxidase – Se-GPx and total glutathione peroxidases T-GPx activities), biotransformation metabolism (glutathione-S-transferases - GST), lipid peroxidation (LPO) and genotoxicity (DNA damage). Biological effects of the mixtures of anticancer compounds on N. diversicolor were compared with previous studies about effects on the same biological model under single-drug exposure conducted with the same molecules. Regarding SOD activity, TAM showed an antagonist effect over CisPt and CP in mixtures C and D. In Mix D, there was a synergistic effect of TAM and CisPt that inhibited CAT activity and an additive interaction of CisPt and CP on the Phase II biotransformation enzyme. Drugs in Mix A also suppressed polychaetes' GST activity, although different from the respective single-drug responses, besides able to induce T-GPx activity, that was not sufficient to avoid oxidative damage and mid-grade DNA damage. Due to the absence of burrowing impairment in Mix A, mechanisms involved in neurotoxicity were other than the one driven by AChE alterations. At the intermediary concentrations (Mix B and C), only LPO occurred. Data from drugs individually may not predict the risks provided by mixtures. Toxicity caused by interactions of anticancer drugs in polychaetes Nereis diversicolor may not be predicted by single-drug exposures.
Keywords: Anticancer drugs; Marine; Mixtures; Sediment; Toxicity